2018
DOI: 10.1016/j.ejbas.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Cancer preventive and therapeutic effects of EGCG, the major polyphenol in green tea

Abstract: (-)-epigallocatechin-3-gallate (EGCG), the major bioactive catechin in green tea (GT) has been studied for almost past thirty years as an agent initially for its cancer chemoprevention effects and then for its cancer chemotherapeutic ability. This agent has shown considerable anti-cancer effects in a variety of preclinical cell culture and animal model systems. However, its clinical application to human patients is hampered by a variety of reasons that includes its stability and bioavailability. As a result, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 180 publications
(314 reference statements)
0
52
0
2
Order By: Relevance
“…Green tea contains a number of biologically active compounds, which include (-)-epicatechin (EC), (-)epicatechin-3-gallate (ECG), (-)-epigallocatechin (EGC), and (-)-epigallocatechin-3 gallate (EGCG) (Rady et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green tea contains a number of biologically active compounds, which include (-)-epicatechin (EC), (-)epicatechin-3-gallate (ECG), (-)-epigallocatechin (EGC), and (-)-epigallocatechin-3 gallate (EGCG) (Rady et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Around 59% of the total catechin from the leaves of the green tea is (-) epigallocatechin-3 gallate (EGCG) (Rady et al, 2018). The radical scavenging ability of EGCG was higher than other catechins because EGCG has the number of hydroxyl groups much more than others.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoprevention approach, especially with the aid of phytochemicals that can hampered the carcinogenesis process at one or multistep, is an ideal method against cancer management . Among natural compounds, diverse number of secondary metabolites extracted from the leaves and buds of the Camellia sinensis (green tea) have been demonstrated to be beneficial for the human health including prevention of several types of cancer . For instance, polyphenolic catechins contained in green tea has been reported for apparent activity against cancer including to promote apoptosis, arrest metastasis by inhibiting metalloproteinases, impair angiogenesis and reverse multidrug resistance .…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer effects of green tea and its products are supported by a large amount of evidence for cell culture and animal models research (Fujikia & Suganuma, ; Kou, Kirberger, Yang, & Chen, ). Furthermore, epidemiological studies indicated that dietary intake of tea may prevent and reduce the risk of different types of malignancies, including liver cancer (Rady, Mohamed, Rady, Siddiqui, & Mukhtar, ). These beneficial effects of green tea are primarily attributed to the presence of a type of polyphenols known as catechins and its monomer, including epigallocatechin‐3‐gallate (EGCG), epigallocatechin (EGC), epicatechin gallate (ECG), epicatechin (EC), and catechin.…”
Section: Introductionmentioning
confidence: 99%
“…Some mechanisms for modulating cancer signaling and metabolic pathways with EGCG have been proposed based on numerous studies in cells, such as TNF, PI3K/Akt/mTOR, p53, p38 MAPK, and NF‐κB pathways (Chan, Lee, Wang, Yeh, & Liang, ; Elguindy, Yacout, El Azab, & Maghraby, ; Li et al, ; Rady et al, ; Wang, Wang, Wan, Yang, & Zhang, ). Our previous studies also found that EGCG, as well as EC, ECG, and EGC, may bind to some cancer‐related proteins in TPK‐RAS‐MAPK and NF‐κB signaling pathways when used molecular docking of these bioactive substances (Zheng, Chen, & Lu, ).…”
Section: Introductionmentioning
confidence: 99%